The Audience’s Perception of Bumi Manusia Film by Hanung Bramantyo: The Adaptation of Bumi Manusia Novel into Film - Hikmawati, Nurul; Fajar Arief, Nur; Ambarwati, Ari (Universitas Negeri Semarang, 2022)
In the current modern era, the pace of development of the literary world becomes more varied, innovative, and creative in literature, one of which is through film media. The novel adaptation is in great demand by the millennial generation today, especially if the film is played by actors who are on the rise. It is undeniable that the selection of actors also affects the outcome of the film is adapted. Research that carried literary adaptation and the perception of readers of the Bumi Manusia novel. This research was descriptive qualitative research that explained the description of the audience's perception of the Bumi Manusia film. The purpose of the researcher using this qualitative approach was to facilitate the research carried out because the data obtained were in the form of writing. The results showed: (1) the perception of the readers of the Bumi Manusia novel and the audience of the Bumi Manusia film said that the cast of Minke, Annelies, and Nyai Ontosoroh in the Bumi Manusia film managed to play their roles well. The role of women was shown to be quite diverse, the representation of independent, intelligent, firm women was shown by Nyai Ontosoroh, (2) the audience's perception of Bumi Manusia film said that the setting of time, place, and atmosphere in the film was quite in accordance with the novel, there were also variations and additions to several scenes in the film., (3) the audience's perception of Bumi Manusia film said that Hanung Bramantyo as the director has succeeded in adapting the Bumi Manusia novel, with the limitations and advantages of a film, Hanung managed to package 19th century-era novels into films that are popular and easy to understand by today's millennials.